Smart Toys for Game-based and Toy-based Learning A Study of Toy Marketers', Preschool teachers' and Parents' Perspectives on Play - Katriina Heljakka; Pirita Ihamäki (My University, 2022)
Over the next years smart Internet-connected toys are expected to grow significantly in numbers. Our study explores smart toys’ potential to deliver experiences related to playful learning. One key aspect of toys, such as the CogniToys Dino, Fisher-Price’s Smart Toy Bear and Wonder Workshop’s Dash Robot are their game-based and toy-based features and functions, which are suggested to have educational outcomes when used in play. Through a comparative investigation of toy marketers’, preschool teachers’ and the parents’ of preschoolaged children’s perspectives of smart toys potential—and a comparison to the actual play experiences of preschoolers discovered in earlier stages of research, we demonstrate how the educational potential of contemporary smart toys may be categorized into game-based and toy-based affordances that may be employed for specific educational goals in playful learning.
Keywords - game-based learning; Internet of Toys (IoToys); play; preschoolers; smart toys.
CENTRIC 2018 : The Eleventh International Conference on Advances in Human-oriented and Personalized Mechanisms, Technologies, and Services